Introducing “Rebirth” – a Model for Organisational Change and Development - Costa, King; Sekgaphane, Del (My University, 2020)
In divergent ecosystems around the world, there is a desire for visible, integral ecological transformation. A lack of ecological transformation is found within various domains beginning with the self, team, organisation and society, and is partly influenced by the loss of identity both within and without the larger ecology. Notably, the issue of identity and transformation remains a burning platform within the African context, for which the researcher proposes a solution grounded in the Southern relational path of community and reason (Schieffer & Lessem, 2014). In the context of this study, the researcher was invited to lead and transform a wealth banking business unit that had become a liability to the larger banking brand, reflecting the lowest engagement scores at the time. The research design applied was Integral Research Approach (IRA). IRA enables one to ground through an experience which engages auto-ethnography. Kothari (2009) stated that “Research methods refer to the behavior and instruments used in selecting and constructing research technique.” In simple terms, this means that research methods refer to the methods the researchers use in research operations.” The applicable ontology was phenomenology, adopting Southern, communal frames from which to drive inclusive transformation, and the epistemology was feminism, encompassing integral research and participatory action research (PAR) as part of the Southern path. Data was gathered by qualitative means such as participative observations, community engagements, discussions and interviews. The researcher analyzed the gathered data by measuring its quality in terms of valuable and truthful results of REBIRTH data analysis. REBIRTH is an innovative organisational change and development process located in the South, and has potential to be adapted and applied within divergent organisations and systems as the rebirth transformation journey. Conclusion of the research culminated in the creation of a REBIRTH Model for Organisational Change and Development, hereinafter referred to as REBIRTH. The purpose of this model’s design is to cause inclusive transformation though enabling an organisation to re-engage the issue of identity as catalyst for inclusivity. It is a creative experience which starts in the Southern relational path, and unfolds into the four voices of global exploration, towards inclusive transformation and authentic identity. REBIRTH reconnects self, other, community and organisation to identity in Botho-Ubuntu, captured in the banking case study vision as: “I Care (Heart), I Can (Head), I Commit. Botho-Ubuntu is an African philosophy which draws us back to the value of our humanness and offers an authentic lens through which to view transformational practice.
Keywords: Change Management; Emotional Intelligence; Leadership; Moral Intelligence; Rebirth; Spiritual Intelligence